PENGARUH MODEL PEMBELAJARAN GROUP INVESTIGATION TERHADAP HASIL BELAJAR BIOLOGI DITINJAU DARI TINGKAT KREATIVITAS SISWA KELAS X SMAN 2 KARANGANYAR - Richvana, Aulia; Dwiastuti, Sri; Prayitno, Baskoro Adi (P Biologi FKIP UNS Surakarta, 2012)
ABSTRACT - This research aimed to know, (1) The existence of significant influence?s Group Investigation model towards the results study of Biology class X SMAN 2 Karanganyar, (2) The existence of significant influence?s creativity level towards the results study of Biology students in class X SMAN 2 Karanganyar, (3) The interaction of significant influence?s between Group Investigation model and creativity level towards the results study of Biology students in class X SMAN 2 Karanganyar. This research is Quasi Experimental Research. Subject in this research are students class X SMAN 2 Karanganyar semester I academic year 2011/2012. Sample in this research are 2 class there are class X2 as control class and class X4 as experiment class. Technique of data collection test, questionnaire and observation sheet. Test is used to measure of cognitif domain and student creativity level, questionnaire is used to measure of afective domain, and observation sheet is used to measure of psikomotoric domain. Technique of data analysis use two ways Varians Analysis (ANAVA) and continuation test use double comparation Scheffe method. Based the result of this research can conclude are, (1) there is significant influence using learning model Group Investigation towards the results study of Biology, (2) there is significant influence creativity level students towards the results study of Biology, (3) there is no interaction of significant influence?s between Group Investigation model and creativity level towards the results study of Biology. The result of continuation test use Scheffe method can conclude are, (1) there is significant influence between column A1 (using Group Investigation model) and column A2 (using Conventional model) towards the results study of Biology, and (2) there is significant influence between row B1 (high level creativity) and row B2 (low level creativity) towards the results study of Biology. The case must be concern in implementation of learning model Group Investigation for research to be effective are students psychological factors like as readiness students capability to learning be autonomous and the students anxienty with sub topic for investigated. Keywords: Group Investigation, Creativity, Result Study of Biologi